2016
DOI: 10.1097/mpa.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features and Germline Sequence Variants in Young Patients (≤40 Years Old) With Pancreatic Ductal Adenocarcinoma

Abstract: The clinicopathologic features in young patients were generally similar to those in older patients. The rarity of family history of PDAC and the sequencing analysis for germline variants suggest that hereditary factors might have a weak, if any, relationship with early-onset PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…The main differences between the two PDAC groups were seen in demographic data. EOPC patients in our population were more frequently males, in agreement with previous studies [ 5 – 7 , 12 , 13 , 36 , 37 ]. In addition, our EOPC patients were less frequently of white British background and more commonly Asian or from ‘any other white background’.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The main differences between the two PDAC groups were seen in demographic data. EOPC patients in our population were more frequently males, in agreement with previous studies [ 5 – 7 , 12 , 13 , 36 , 37 ]. In addition, our EOPC patients were less frequently of white British background and more commonly Asian or from ‘any other white background’.…”
Section: Discussionsupporting
confidence: 93%
“…While the overall survival of EOPC was similar to older PDAC patients with no statistically significant difference, EOPC patients who underwent surgical resection had a longer median overall survival of 25 months compared to 13 months for the same PDAC subpopulation. A similar finding has been observed in previous studies, with the highest survival of 41.8 months for resected cases reported by Duffy et al [ 10 ] which has been attributed to young people having fewer comorbidities and being more suitable candidates for surgery and adjuvant chemotherapy [ 10 , 12 , 13 , 36 , 37 ]. Furthermore, He et al also showed that EOPC patients had fewer post-operative complications [ 12 ] and McWilliams et al, [ 14 ] attributed the better survival rate among young people to a multitude of factors, including race, sex, year of diagnosis, stage of disease, tumour location and treatment [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When considered this signature in the clinical set, the predictive value was also robust in different subpopulation. Studies indicated early and late onset pancreatic cancer suffered different genomic alteration and clinicopathologic features (McWilliams et al, ; Ohmoto et al, ). Survival analysis in the TCGA cohort was not available to support this point, but our risk model was both feasible in patients with diagnostic age larger or <50 (Figure ).…”
Section: Discussionmentioning
confidence: 99%